Internal control and tax avoidance: A possible mitigation effort - Rakhmayani, Alfita; Aresteria, Maya; Sulestiyono, Deddy (Proceeding International Conference on Accounting and Finance, 2024)
Companies view taxes as a cost that has the potential to reduce profits. Tax avoidance is a company’s action to reduce the amount of tax that must be paid in a legal way. This paper aims to provide an analysis of the potential for reducing tax avoidance through internal controls implemented by companies through literature studies. The study was carried out by selecting relevant literature, analysis as well as mapping and interpretation of the results. Based on the dominance of the findings, it can be considered that effective internal control has the potential to prevent aggressive tax avoidance by companies.